The European Union in the security of Europe from Cold War to terror war - Marsh, Steve (Routledge, 2012)
A new and comprehensive guide to the European Union's role and development in European security since the end of the Cold War, which explores the interface between the EU and other organizations and other states, specifically NATO, the US and Russia. Engaging in key debates in international security, the authors trace the history of the EU as a security actor and explore a broad range of contemporary security issues concerning the EU. * Part 1 examines the post-Cold War security evolution of the EU, focusing on the German, British and French foreign policies. It explores the Anglo-Franco-German relationship, the Anglo-American relationship and the EU-US relationship * Part 2 investigates contemporary EU security issues such as legitimacy, immigration and asylum, environmental security, interventionism, and internal and external institutional synergy. * Part 3 explores four case studies of the EU in action: Iraq, the Balkans, the 'war' on terrorism and the stabilization of Central and Eastern Europe.